The establishment of sub-strain specific WHO Reference Reagents for BCG vaccine - Dagg, Belinda (Vaccine, 2014)
As the latest addition to the sub-strain specific WHO Reference Reagents of BCG vaccine, an international collaborative study was completed to evaluate the suitability of a candidate BCG Moreau-RJ sub-strain as a WHO Reference Reagent of BCG vaccine. This follows the recent replacement of the WHO 1st International Reference Preparation for BCG vaccine, by three sub-strain specific WHO Reference Reagents of BCG vaccine (Danish 1331, Tokyo 172-1 and Russian BCG-I) in order to complete the coverage of most predominant sub-strains used for BCG vaccine production and distribution for use worldwide. The study used cultural viable count and modified ATP assays to quantify the preparation and multiplex PCR to confirm the identity of the sub-strain. The establishment of this WHO Reference Reagent of BCG vaccine of Moreau-RJ sub-strain was approved by the WHO Expert Committee on Biological Standardization meeting in October 2012. This preparation is available for distribution by NIBSC-MHRA, UK. The data from real-time stability monitoring demonstrated that these Reference Reagents of BCG vaccine are very stable in storage condition at −20 °C. They serve as the valuable source of BCG Reference Reagents for use as comparators (1) for viability assays (such as cultural viable count and modified ATP assays); (2) for in vivo assays (such as the absence of virulent mycobacteria, dermal reactivity and protection assays) in the evaluation of candidate TB vaccines in non-clinical models; (3) for identity assays using molecular biology techniques.